Orthodontic Management of Skeletal Class II Malocclusion with the Invisalign Mandibular Advancement Feature Appliance: A Case Report and Review of the Literature - Melina Koukou; George Damanakis; Apostolos I. Tsolakis (Hindawi Limited, 2022)
The treatment of Class II malocclusion due to mandibular retrognathia is one of the most common challenges met in orthodontic practice. When it comes to a growing patient, functional appliances are the optimal way to achieve growth modification by enhancing mandibular growth. Clear aligners have been part of the orthodontic treatment for several decades but until recently they were only used to correct mild malocclusions. In 2017, Align Technology introduced the Invisalign with Mandibular Advancement Feature (IMAF) which replicates the action of functional appliances. As this device is new to clinical practice, there is limited literature on its clinical efficiency. This case report describes the orthodontic management of a 12-year-old male patient having skeletal Class II malocclusion due to mandibular retrognathia. As the patient was experiencing active growth, the IMAF appliance was chosen for his treatment. The IMAF appliance appears to be successful in the treatment of Class II malocclusion with mandibular retrognathism in a growing patient. As with all functional appliances, the correction of the malocclusion is a result of both skeletal and dental effects and the IMAF presents the advantage of producing less proclination of the lower incisors compared to other functional appliances.